Analisis Keunggulan Kompetitif Perbankan Syariah di Indonesia - Utari Evy Cahyani (Institut Agama Islam Negeri Padangsidimpuan, 2017)
Based on the result of research indicate that there is linkage between component of porter diamond model in sharia banking industry in Indonesia. The linkages are supportive and non-supportive. Supportive linkages exist in resource conditions, government role, role of opportunity. While the relationship is not supportive that is on the factors of competition and corporate strategy.